Water Washing Pretreatment On Empty Fruit Bunches Of Oil Palm Waste - Khalib, Nuridayanti Che (2011)
The water washing pretreatment on empty fruit bunches (EFB) of oil palm waste has been investigated in this study, with the objective of removing some ash from the EFB to improve the quality of biomass. This study also investigated the effectiveness of water washing to remove ash by changing the appropriate parameters of the water washing pretreatment such as residence time, amount of water, type of water and use of soaking and stirring. Tap water and distilled water were solely used throughout the work.